Searching for Vanadium‐Based Prospective Agents against Trypanosoma cruzi: Oxidovanadium(IV) Compounds with Phenanthroline Derivatives as Ligands1. Issue 8 (28th March 2013) - Benítez, Julio; Correia, Isabel; Becco, Lorena; Fernández, Mariana; Garat, Beatriz; Gallardo, Hugo; Conte, Gilmar; Kuznetsov, Maxim L.; Neves, Ademir; Moreno, Virtudes; Costa Pessoa, João; Gambino, Dinorah
Abstract Searching for new promising metal‐based drugs for the treatment of parasitic diseases against Trypanosoma cruzi, three related oxidovanadium(IV) complexes, [VIVO(SO4)(H2O)2(NN)], with the phenanthroline derivatives (NN) 1, 2, 5thiadiazolo[3, 4‐f]1, 10phenanthroline (tdzp), 1, 10‐phenanthroline‐5, 6‐dione (phendione), and 5, 6‐epoxy‐5, 6‐dihydro‐1, 10‐phenanthroline (epoxyphen) are synthesized, characterized, and evaluated in vitro as anti‐T. cruzi agents. The compounds are characterized in the solid state and in solution by elemental analysis, electrospray ionization mass spectrometry (ESI‐MS), conductimetric measurements, and infrared (FTIR), UV/Vis, and electronic paramagnetic resonance (EPR) spectroscopy. EPR spectroscopy suggests that the ligands act as bidentate, binding through both nitrogen donor atoms in an axial‐equatorial mode. DFT calculations corroborate the structural assignments. The stability of the complexes in solution is evaluated by EPR and 51V‐ NMR spectroscopy and all complexes show reasonable stability. The anti‐T. cruzi activity of the complexes was tested by measuring the growth inhibitory effect on the epimastigote life cycle form of the parasite (Dm28c strain). All complexes show IC50 values in the micromolar range against T. cruzi and display activities of the same order of that of Nifurtimox, but lower than that of the previously reported analogue [VIVO(SO4)(H2O)2(dppz)] (dppz = dipyrido[3, 2‐a:2′, 3′‐c]phenazine). Furthermore, DNA was evaluated as a potential target by using atomic force microscopy (AFM), showing that the complexes display ability to interact with this biomolecule.